Effect of Homogenization Pressure on Bacterial Cellulose Membrane Characteristic Made from Pineapple Peel Waste - Muhamad Muhajir; Heru Suryanto; Yanuar Rohmat Aji Pradana; Uun Yanuhar (Journal of Mechanical Engineering Science and Technology (JMEST), 2022)
Many studies were conducted to maintain the environment by reducing the waste, especially pineapple peel waste. This study aims to explore the effect of various pressure of the homogenization process on bacterial cellulose membrane surface morphology and structure produced using extract of pineapple peel waste. The methods include the preparation of pellicle samples from the product of the fermentation process of Acetobacter xylinum using a medium from the extract of pineapple peel waste. Bacterial cellulose pellicles were crushed using a blender. Mashed bacterial cellulose pellicle then homogenized in High-Pressure Homogenizer with pressure variation of  0 bar, 150 bar, 300 bar, 450 bar, dan 600 bar then cast into a mold. The bacterial cellulose solutions were dried in an oven at 60°C for 8 hours. The dried bacterial cellulose membrane was analyzed using XRD for the structure and SEM analysis for the morphology. The results indicate that the crystalline properties of BCM were shifted after being treated by various pressure processing in a High-Pressure Homogenizer. It was found that the High-Pressure Homogenizer with higher pressure reduced the peak intensity, decreased crystalline index from 87% to 70%, and decreased the degree of crystalline from 88% to 77%  without changing the cellulose structure. The higher pressure of the homogenization process causes the porosity of the membrane to be decreased.